Low temperature characteristics of germanium whiskers - Druzhinin, A.A.; Ostrovskii, I.P.; Khoverko, Yu.N.; Liakh-Kaguy, N.S.; Vuytsyk, A.M. (Functional Materials, 2014)
Magnetophonone oscillations of magnetoresistance in heavily doped n-Ge whiskers with impurity concentration that corresponds to metal-insulator transition were studied in the temperatures range 4.2-70 K in continuous and pulse magnetic fields up to 14 T and 35 T, respectively. The influence of uniaxial compressive and tentative strain on the magnetophonon oscillations of longitudinal and transverse magnetoresistance of n-Ge whiskers were studied, the intervalley transitions were determined, phonon energy as well as the effective masses of light and heavy electrons in n-Ge whiskers were estimated. Ge whiskers were used for creation of strain-temperature sensors, operating in high magnetic fields and at low temperatures.